2019
DOI: 10.3390/su11020369
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Willingness and Influencing Factors on Action Personal Carbon Trading: A Case Study of Metropolitan Areas in Tianjin, China

Abstract: Personal carbon trading offers a powerful and innovative instrument with which to achieve reductions in carbon emissions. Meanwhile, residents’ personal carbon trading willingness and the factors influencing such willingness have critical effects on the acceptance of personal carbon trading. Therefore, the present research uses a questionnaire survey in metropolitan areas of Tianjin China and the results indicated that most of the interviewees (74.92%) agreed or strongly agreed that they would participant in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…For example, 13% of the college students and residents in Cambridge, United Kingdom expressed support for a PCT scheme [ 12 ]. In Tianjin, China, 74.92% of the residents agreed to participate in the PCT [ 14 ]. Tianjin is located in the eastern part of China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 13% of the college students and residents in Cambridge, United Kingdom expressed support for a PCT scheme [ 12 ]. In Tianjin, China, 74.92% of the residents agreed to participate in the PCT [ 14 ]. Tianjin is located in the eastern part of China.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the various advantages of the PCT scheme, the feasibility of its implementation largely depends on the behavioral willingness of its participants; that is, residents [ 11 ]. The evidence shows that residents’ behavioral willingness to accept and participate in the scheme could be influenced by individual factors; these include the cognition of climate change [ 12 ], perception of environmental threat [ 13 ], expected behaviors for energy conservation and emissions reduction [ 13 ], and environmental awareness [ 14 ]. The scheme itself also affects residents’ attitudes, such as the pattern for implementing the scheme [ 5 ], the method for allocating the initial carbon allowance [ 15 ], and the household activities included in the measurement of the carbon emissions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Country-specific characteristics could make PCTS more or less feasible [60]. These could be technical limitations, which can be an issue for the least developed and developing countries, but also cultural aspects of the general opinion on climate change [61]. In addition, the type of regime (democracy or autocracy) can have an impact on a country's ability to take climate mitigation action [62].…”
Section: Discussionmentioning
confidence: 99%
“…Influences of carbon trading on personal behavior were analyzed in a number of studies, for example, Kuokkanen et al (2020) found that carbon neutrality knowledge and income have a positive impact on personal carbon trading. Liu (2019) indicated that government policies, residents' environmental awareness and motivation are positively correlated with their willingness to personal carbon trading. Zhang and Feng (2022) uses logit modeling to analyze the effect of attributes on individuals' willingness to participate in personal carbon trading in the context of carbon-neutral policies as well as the effect of public heterogeneity on personal carbon trading.…”
Section: Green Travel Behavior and Personal Carbon Tradingmentioning
confidence: 99%
“…Zhang and Feng (2022) uses logit modeling to analyze the effect of attributes on individuals' willingness to participate in personal carbon trading in the context of carbon-neutral policies as well as the effect of public heterogeneity on personal carbon trading. Evidence suggests that residents' behavioral willingness to accept and participate in the program may be influenced by personal factors, such as perceptions of climate change, perceived environmental threats, and environmental awareness (Xie et al, 2014;Liu, 2019). Tan et al (2019) investigated the driving factors of the public's willingness to participate in individual carbon trading in Guangdong pilot project, and the results showed that the institutional and technical environment, social reference norms, low-carbon cognition, participation feedback and participation risk were the influencing factors of public support for individual carbon trading.…”
Section: Green Travel Behavior and Personal Carbon Tradingmentioning
confidence: 99%